Enhanced performance of CsPbIBr2 perovskite solar cell by modified zinc oxide nanorods array with [6,6]‐Phenyl C61 butyric acid - Yang, Jien; Zhang, Meng; Zhang, Qiong; Qin, Chaochao; Qin, Ruiping; Jain, Sagar M.; Liu, Hairui (Wiley, 2023)
Although Metal oxide ZnO is widely used as electron transport layers in all-inorganic PSCs due to high electron mobility, high transmittance, and simple preparation processing, the surface defects of ZnO suppress the quality of perovskite film and inhibit the solar cells’ performance. In this work, [6,6]-Phenyl C61 butyric acid (PCBA) modified zinc oxide nanorods (ZnO NRs) is employed as electron transport layer in perovskite solar cells. The resulting perovskite film coated on the zinc oxide nanorods has better crystallinity and uniformity, facilitating charge carrier transportation, reducing recombination losses, and ultimately improving the cells’ performance. The perovskite solar cell with the device configuration of ITO/ZnO nanorods/PCBA/CsPbIBr2/Spiro-OMeTAD/Au delivers a high short circuit current density of 11.83 mA cm-2 and power conversion efficiency of 12.05 %.
Keywords: Zinc oxide nanorods; inorganic CsPbIBr2 perovskite solar cell; interface modification; [6,6]-Phenyl C61 butyric acid